House Ventilation Area and Covid-19’s Household Transmission in The Region of Pemurus Dalam Health Centre Banjarmasin - Farida Heriyani (Berkala Kedokteran, 2022)
The occurance of COVID-19 is still increasing, especially in Banjarmasin. The increasing number of COVID-19 cases is caused by several factors, including the presence of household transmission from COVID-19 patients to other people in their homes. This household transmission can be affected by the ventilation area of the house. This study aims to analyze the relationship between the area of house ventilation and the occurance of COVID-19 transmission of at home in the in the region of Pemurus Dalam Health Centre Banjarmasin. The research method was analytic observational with a cross sectional approach. The research sample was confirmed COVID-19 patients based on PCR results and recorded at the Pemurus Dalam Health Center. Sampling using simple random sampling technique with a sample of 50 patients. Data analysis used chi square test at 95% confidence level. The results showed that there were 26 people (76.4%) of the research subjects who lived in a house with a house ventilation area that did not meet the requirements (<10% of the house area). Meanwhile, in the research subjects who lived in houses with adequate ventilation area (≥10% of the house area) only 4 people (25%) had household transmission. The analysis results showed that there was a significant relationship between the ventilation area of the house and the occurrence of COVID-19 household transmission in the Pemurus Dalam Health Center area of Banjarmasin (p = 0.001 and RR 3.24).